Stan zachowania gatunków drzew rosnących na rekultywowanych powierzchniach wyrobisk Śląskich Zakładów Przemysłu Wapienniczego ,,Opolwap" S.A. = Health state tree species growingon reclaimed surfaces of the opencast working of "Opolwap" S.A. Silesian Lime Works - Kusza, Grzegorz; Dużyński, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Opole Voivodeship is characterized by large carbonale rock beds occurring within the area of the region. They have been exploited as raw materials for cement-lime industry purposes. However, lime exploitation is connected with tremendous geomorphological reshaping of land surface.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)